Comprehensive Analysis of Micronutrients in Different Blocks of Kaithal District, Haryana - Mohit Sharma; R.S. Garhwal; Anil Kumar; S.K. Dubey; Amit Kumar; Jyoti Sheoran; Harsh (Journal of the Indian Society of Soil Science, 2025)
Developing site-specific nutrient management techniques requires a deep understanding of the spatial diversity in soil fertility. This study was carried out in the Kaithal district, focusing on the regions of Kalayat, Rajound, Pundri and Dhand. In this study, a total of 212 soil samples were collected from a depth of 0-15 cm in arable land of 106 different villages in the Kaithal district by using GPS, and the data was subsequently mapped using GIS (Arc GIS 10.2). The findings indicated that the soils in all four blocks exhibited a neutral to alkaline pH and were non saline in character. The mean content of available micronutrients (Zn, Fe, Mn and Cu) in the Kalayat block was 1.44, 8.66, 3.29 and 1.06 mg kg-¹, respectively. In the Rajound block, these values were 1.47, 7.15 3.67 and 1.15 mg kg-¹; in Dhand block, they were 2.10, 7.53, 3.46 and 1.22 mg kg-¹; and in Pundri block, they were 2.33, 9.53, 3.23 and 1.13 mg kg-¹, respectively. Out of total samples, 36% were classified to be Mn-deficient, 57% to be latently deficient, and 7% to be marginally sufficient. Results have revealed that the DTPA – extractable Cu, Mn, Fe and Zn did not show any significant relationship with soil pH and electrical conductivity (EC).